Transcriptional regulation of the human ferritin gene by coordinated regulation of Nrf2 and protein arginine methyltransferases PRMT1 and PRMT4 - Huang, Bo-Wen (Federation of American Societies for Experimental Biology, 2013)
Antioxidant genes such as ferritin are transcriptionally activated in oxidative stress via the antioxidant responsive element (ARE), to which nuclear factor-E2-related factor 2 (Nrf2) binds and activates transcription. Histone modification plays a cooperative and essential role in transcriptional regulation; however, its role in antioxidant gene transcription remains elusive. Arsenic exposure activated ferritin transcription via the ARE concomitant with increased methylation of histones H4Arg3 (H4R3) and H3Arg17 (H3R17). To test our hypothesis that histone H4R3 and H3R17 methylation regulates ferritin transcription, H4R3 and H3R17 protein arginine (R) methyltransferases 1 and 4 (PRMT1 and PRMT4) were investigated. Arsenic exposure of human HaCaT keratinocytes induced nuclear accumulation of PRMT1 and PRMT4, histone H4R3 and H3R17 methylation proximal to the ARE, but not to the non-ARE regions of ferritin genes. PRMT1 or PRMT4 knockdown did not block Nrf2 nuclear accumulation but inhibited Nrf2 binding to the AREs by ∼40% (P<0.05), thus diminishing ferritin transcription in HaCaT and human primary keratinocytes and fibroblasts, causing enhanced cellular susceptibility to arsenic toxicity as evidenced by 2-fold caspase 3 activation. Focused microarray further characterized several oxidative stress response genes are subject to PRMT1 or PRMT4 regulation. Collectively, PRMT1 and PRMT4 regulate the ARE and cellular antioxidant response to arsenic.—Huang, B.-W., Ray, P. D., Iwasaki, K., Tsuji, Y. Transcriptional regulation of the human ferritin gene by coordinated regulation of Nrf2 and protein arginine methyltransferases PRMT1 and PRMT4.